Effectiveness of Community Treatment Orders: The International Evidence: Efficacité des ordonnances de traitement en milieu communautaire: Les données probantes internationales - Rugkåsa, Jorun (Can J Psychiatry, 2016)
OBJECTIVE: Community treatment orders (CTOs) exist in more than 75 jurisdictions worldwide. This review outlines findings from the international literature on CTO effectiveness. METHOD: The article draws on 2 comprehensive systematic reviews of the literature published before 2013, then uses the same search terms to identify studies published between 2013 and 2015. The focus is on what the literature as a whole tells us about CTO effectiveness, with particular emphasis on the strength and weaknesses of different methodologies. RESULTS: The results from more than 50 nonrandomized studies show mixed results. Some show benefits from CTOs while others show none on the most frequently reported outcomes of readmission, time in hospital, and community service use. Results from the 3 existing randomized controlled trials (RCTs) show no effect of CTOs on a wider range of outcome measures except that patients on CTOs are less likely than controls to be a victim of crime. Patients on CTOs are, however, likely to have their liberty restricted for significantly longer periods of time. Meta-analyses pooling patient data from RCTs and high quality nonrandomized studies also find no evidence of patient benefit, and systematic reviews come to the same conclusion. CONCLUSION: There is no evidence of patient benefit from current CTO outcome studies. This casts doubt over the usefulness and ethics of CTOs. To remove uncertainty, future research must be designed as RCTs.